Internet Users’ Beliefs about a Novice-user of Child Sexual Abuse Material (CSAM): What Can They Tell Us about Introducing Offender-focused Prevention Initiatives? - Hunn, Charlotte (Victims & offenders, 2022)
Interest in preventing child sexual abuse material (CSAM) offending is growing. A variety of initiatives have been proposed, including the use of warning messages triggered by keyword searches. An under-explored question is how the public might perceive such initiatives. Existing research reveals that the public holds very negative views about individuals labeled ‘sex offenders’ and ‘pedophiles’. Yet, little is known about how the public views individuals who commit CSAM offenses. This study explores the beliefs of 491 young adult Internet users toward a hypothetical novice-user of CSAM. Using thematic analysis, five key themes are identified. Informed by this analysis, implications for introducing prevention initiatives are discussed.